The midnight library - Haig, Matt,Mulligan, Carey (Bolinda audio, 2020)
Somewhere out beyond the edge of the universe there is a library that contains an infinite number of books, each one the story of another reality. One tells the story of a person's life as it is, along with another book for the other life they could have lived if they had made a different choice at any point in their life. While everyone wonders how their lives might have been, what if someone had the chance to go to the library and see for them self? Would any of these other lives truly be better?
Keywords: Fictional Work; Libraries; Choice (Psychology); Regret; Decision making; Audiobooks; Novels; Fiction; Livres audio; Romans